Analysis of Risk Factors for Fire Protection - Febri Anindita Suralaga; Nurhalina Sari; Dina Dwi Nuryani; Samino (Postgraduate, University of Mataram, 2024)
Active fire protection system in RSD. A. Dadi Tjokrodipo Bandar Lampung has not met the standards related to the Technical Requirements for Fire Protection Systems. Inside the building there is an alarm system and fire protection system that is not maintained and not functioning, there are no automatic sprinklers installed in the room, and there is no fire extinguishing system installed. permanent and uneven. The aim of this research is to determine the suitability analysis of RSD active fire protection system facilities. Dr.A Dadi Tjokrodipo, Bandar Lampung City, 2023. The aim of the research is to determine the risk factors for fire protection at RSD Dr. A. Dadi Tjokrodipo Bandar Lampung. This type of qualitative descriptive research uses an observation and documentation interview approach. The total sample was 4 respondents using purposive sampling technique. The research results show that active fire protection facilities are APAR, alarm, detector, sprinkler and hydrant with a total of 43 indicators, consisting of APAR (13 indicators), 12 indicators (90%) are met, 1 indicator (10%) is not met. . Of all these indicators. RSD dr. Dadi Tjokrodipo, Bandar Lampung City, 12 indicators were met (5.16%) and 34 (94.84%) other indicators were not met. It can be concluded that hospital fire response readiness in dealing with potential fires is still minimal and inadequate. It is hoped that the hospital will continue to improve the quality of facilities and infrastructure.